Comparative Efficacy of Low-Dose Oral Corticosteroids and Oral Mini Pulse Dexamethasone in Patients of Vitiligo (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Vitiligo is a common, acquired, discoloration of the skin with unknown etiology. There are numerous treatment options available for vitiligo, but none is universally effective. Systemic corticosteroids suppress immunity and lead to repigmentation but produce unacceptable side effects. Oral corticosteroid low dose treatment may be associated with fewer side effects than usual dose-treatment. Several data also showed that oral dexamethasone pulse treatment was effective in arresting progression of vitiligo yet fails to induce satisfactory repigmentation in the great majority of their patients.Objectives: A clinical trial was carried out to compare the efficacy of low-dose oral corticosteroids and oral mini pulse dexamethasone in patients of vitiligo.Materials and Methods: The study was conducted in the Department of Dermatology and Venereology, Combined Military Hospital (CMH), Dhaka, Bangladesh during January 2013 to December 2013. Total sixty patients of vitiligo were enrolled and divided into group A and group B. Thirty of group A patients were treated with oral prednisolone daily and thirty of group B patients were treated with oral dexamethasone pulse therapy weekly.Results: Out of sixty patients of vitiligo, maximum patients of both groups had progressive type of vitiligo. In Group-A, the duration of illness was an average of 10 months and in group-B, it was an average of 8.20 months. Single lesion was 15 (50%) for Group-A and 14 (46.7%) for Group-B. Multiple lesions were 15 (50%) & 16 (53.6%) for Group-A and Group-B respectively. The study showed that improvement rate was highest for the lesions on the extremities, which was 18 (34.6%) and lowest for back 03 (5.8%). Out of all patients from Group-A, the mean size of the lesions were 8.17cm, 5.90 cm, 4.32 cm and 3.57 cm at 1st visit, 2nd visit, 3rd visit and 4th visit respectively. In Group-B, the mean sizes of the lesions were 7.50 cm, 4.92 cm, 3.00 cm, and 4.75 cm at 1st visit, 2nd visit, 3rd visit and 4th visit respectively. Among the patients 27 (90%) of group-A and 25 (83.3%) of group B were improved after 16th week of treatment, slight response 4(13.3%) and 6(20%), moderate response 22(63.2%) and 18(59.4%) and marked response was 1(3.3%) and 1(3.3%) in group A and group B respectively.Conclusion: The study concluded that both the drugs, oral prednisolone and dexamethasone when used individually, were found to be equally effective in the treatment of vitiligo.Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 54-58